2011
DOI: 10.4103/0974-777x.83531
|View full text |Cite
|
Sign up to set email alerts
|

Minimal inhibitory concentration of ceftazidime and Co-trimoxazole for Stenotrophomonas maltophilia using E-test

Abstract: BackgroundStenotrophomonas maltophilia, previously named as Pseudomonas or Xanthomonas maltophilia, is an important nosocomial pathogenAimThe purpose of the present study was to investigate the prevalence of S. maltophilia in Iranian hospitals and its susceptibility to available antimicrobial agents.Setting and design:A cross-sectional study in Imam Khomeini Hospital affiliated to Tehran University of Medical Sciences.Materials and MethodsAll blood specimens were sent to the laboratory for blood culture and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A study by Jamali et al. showed that susceptibility of S. maltophilia against ceftazidime was 82% with the MIC 50 and MIC 90 values of 2 and 32 μg/ml, respectively (Jamali et al., 2011). Shahla et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Jamali et al. showed that susceptibility of S. maltophilia against ceftazidime was 82% with the MIC 50 and MIC 90 values of 2 and 32 μg/ml, respectively (Jamali et al., 2011). Shahla et al.…”
Section: Discussionmentioning
confidence: 99%
“…Jamali et al. showed about 60% susceptibility rate for TMP-SMX and the MIC 50 and MIC 90 values were 0.5 and 2 μg/ml (Jamali et al., 2011). In our study, based on the CLSI recommended dose of TMP-SMX, the resistance rate of 3.04% and the MIC 50% and MIC 90% values of 2.38 and 4.76 were found, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Farrell et al showed that susceptibility of S. maltophilia against ceftazidime was 32.51% in Latin America, North America, Asian-Pacific, and Europe [ 26 ]. In contrast, Jamali et al reported the susceptibility rate of 82% against this drug [ 27 ]. In our study, 100% and 95.29% of S. maltophilia were susceptible to minocycline and levofloxacin, respectively.…”
Section: Main Textmentioning
confidence: 99%
“…8,10 Some in vitro data also support the use of cefepime, ceftazidime, tigecycline, and ticarcillin–clavulanic acid. 11 -13 To our knowledge, this is the first report of S maltophilia endocarditis that was treated with minocycline as an adjunct to other antibiotics.…”
Section: Introductionmentioning
confidence: 89%